Bridging belief revision and ontology repair: moving closer to optimal repairs - Souza, Davy Alves de (2024)
In Knowledge Representation, the knowledge of an agent can be represented by a belief set. Belief Revision explores methods to handle potential changes in a belief set. The AGM model describes operations of expansion, revision, and contraction, which serve as the foundation for revision models. Some studies demonstrated a close relationship between the field of Belief Revision and Ontology Repair. In this research, we analyze repair methods that are able to construct optimal repairs, comparing their results with those of contraction operations. Additionally, we present a method for saturating knowledge bases, allowing contraction operations to yield results that are closer to optimal repairs.